2018
DOI: 10.1021/acs.analchem.8b01574
|View full text |Cite
|
Sign up to set email alerts
|

Rox-DNA Functionalized Silicon Nanodots for Ratiometric Detection of Mercury Ions in Live Cells

Abstract: A ratiometric fluorescent sensor for mercury ions (Hg) has been constructed via covalent functionalization of silicon nanodot (SiND) with Hg-specific 6-carboxy-X-rhodamine (Rox)-tagged DNA. For the Rox-DNA functionalized SiND, the red fluorescence of Rox can be quenched by the blue-emitting SiND in the presence of Hg due to structural change in DNA, which serves as the response signal. Meawhile, the fluorescence of SiND is insensitive to Hg and acts as the reference signal. The wavelength difference in the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…Our group demonstrated that water-soluble SiNDs can be easily prepared at gram scale by the hydrothermal method [ 20 , 49 ]. Then a series of SiNDs-based ratiometric biosensors were constructed for sensing pH, mucin 1, Hg 2+ , DNA, and dipicolinic acid in human serums or the cellular environment [ 20 , 21 , 22 , 23 , 50 , 51 ]. For example, we developed a ratiometric fluorescent Hg 2+ sensor by covalent modification of SiND with Hg 2+ -specific 6-carboxyX-rhodamine (Rox)-tagged DNA ( Figure 3 A).…”
Section: Nanomaterial-based Ratiometric Fluorescent Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group demonstrated that water-soluble SiNDs can be easily prepared at gram scale by the hydrothermal method [ 20 , 49 ]. Then a series of SiNDs-based ratiometric biosensors were constructed for sensing pH, mucin 1, Hg 2+ , DNA, and dipicolinic acid in human serums or the cellular environment [ 20 , 21 , 22 , 23 , 50 , 51 ]. For example, we developed a ratiometric fluorescent Hg 2+ sensor by covalent modification of SiND with Hg 2+ -specific 6-carboxyX-rhodamine (Rox)-tagged DNA ( Figure 3 A).…”
Section: Nanomaterial-based Ratiometric Fluorescent Biosensorsmentioning
confidence: 99%
“… ( A ) Schematic presentation of the preparation of SiND-DNA-Rox and its application for ratiometric detection of Hg 2+ . Reproduced from [ 23 ], with permission from the American Chemical Society, 2018. ( B ) ( a ) Schematic of Eu@SiNRs sensor, ( b ) TEM image of Eu@SiNRs, ( c ) fluorescence spectra of Eu@SiNRs in PBS buffers with different pH values under 405 nm excitation, ( d ) a Eu@SiNRs-based pH sensor for ratiometric measurements of cytoplasmic pH in live cells.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In addition, Hg poisoning in living organisms is still a hot issue of global concern, as Hg 2+ can easily penetrate biological membranes and cause toxicity. 20,21 Considering that various metal-sensing platforms can only detect limited types of metal ions, 22−24 it is desirable to develop a multifunctional sensing platform for achieving the simultaneous and efficient detection of different types of metal ions to well meet the increased requests of clinical diagnosis and sanitation monitoring systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, developing smart sensors with versatile sensing capabilities and high sensitivity has drawn much interest from the biosensing community. Various sensing platforms have been developed for the efficient detection of different metal elements, which may have the positive and/or negative effects on human bodies. Specifically, Fe and Cu are the essential elements of the human body for numerous physiological and pathological functions. The Bi element has been extensively used for radiotherapeutic, antibacterial, antiulcer, and anti-human immunodeficiency virus (anti-HIV) treatments. , However, abnormal contents of Fe, Cu, or Bi usually cause various diseases, such as anemia, hepatitis, Wilson’s/Alzheimer’s/Parkinson’s disease, or even cancer. For Ag, its excessive content in the body will lead to severe skin problems, stomach pain, nervous system damage, and even death. For Pd, the excess intake of this element will badly affect various cellular processes and result in severe physiological disorders. , In addition, Hg poisoning in living organisms is still a hot issue of global concern, as Hg 2+ can easily penetrate biological membranes and cause toxicity. , Considering that various metal-sensing platforms can only detect limited types of metal ions, it is desirable to develop a multifunctional sensing platform for achieving the simultaneous and efficient detection of different types of metal ions to well meet the increased requests of clinical diagnosis and sanitation monitoring systems.…”
Section: Introductionmentioning
confidence: 99%